Pharmacokinetics of oral lidocaine and nifedipine in patients with liver cirrhosis - Tonsuwannont W. (2014)
The pharmacokinetics of oral lidocaine and nifedipine and hemodynamic effects of nifedipine were studied in 10 cirrhotic patients and 10 healthy volunteers. In a randomized two-way crossover design, each subject received 50 mg of lidocaine solution and 10 mg capsule of nifedipine with one-week washout period. After oral lidocaine, cirrhotic patients has a longer time to peak concentration (Tmax) and elimination half-life (t1/2), and a higher area under the curve (AUC). There were no significant differences in peak plasma concentration (Cmax) and elimination rate constant (K(el)) in the two groups. After oral nifedipine, cirrhotic patients had a longer elimination t1/2, lower K(el) and higher AUC. At peak concentration in cirrhotic patients, there was more decrease in the systolic blood pressure and less increase in heart rate. Although large interindividual variability existed in this study, pharmacokinetic parameters were considerably altered in cirrhotic patients.